Pengembangan Sistem E-Government Untuk Peningkatan Layanan Publik Pada Tata Kelola Administrasi Desa - Winda Sulastri; Dedi Kustiawan; Alfry Aristo Jansen Sinlae; Muhammad Irfan (STMIK Budi Darma, 2021)
The Village Office is the lowest level government agency that carries out public services in the field of population administration based on Law Number 6 of 2014 one of which is in serving community administration. The process of archiving activities at the village office is still done manually using archive books, and archival documents are stored in cabinets or filing places. Likewise, in the community service process, especially in making correspondence, it is still not optimal, due to the limited staff working at the village office so that it takes a long time to process correspondence. In this study, an E-Government system was developed which has the ability to perform digital archives and correspondence so as to improve village administration services. The research started from data collection methods (interviews, observations and documentation) using the prototype development method, making system designs using UML with use case diagrams, activity diagrams and class diagrams. The results of the ISO 25010 test that has been carried out by involving 10 respondents that the conclusion of the quality of the resulting software feasibility has a success percentage with a total average of 95.92%.